FAKTORÔÇôFAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAN YANG MASUK DALAM LQ 45 DI BURSA EFEK INDONESIA PERIODE 2014 - 2016 - jurnalpps pps; Dyah Ayu Cahyaningtyas; Indra Prasetyo; Fatimah Riswati (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
The purpose of this research is to analyze the influence of each variable, DER (debt to equity ratio), ROE (Return On Equity), EPS (Earning Per Share ), ROA (Return On Asset), PBV (Price to Book Value), and PER (Price Earning Ratio) to Share Price entered in LQ 45.Population in this research is all shares of company that entered in LQ 45 period 2014 - 2016 as many as 55 company. While the sample selection technique in this study using purposive sampling method so that obtained 36 research samples of the company. Data analysis method used is multiple linear regression analysis. The results of the analysis found that simultaneously DER, ROE, EPS, ROA, PBV and PER positive and significant to stock price, the result is known through Test F. While partially DER, EPS, ROA, and PBV have positive and significant influence to stock price while ROE have negative and significant effect to stock price but PER variable have positive but not significant stock price. Adjusted R square number of 0.989 indicates that 98.9% share price can be explained by the six independent variables used in the regression equation, while the remaining 1.1% is explained by other variables beyond the six variables used in this study. Keywords: Stock Price, DER, ROE, EPS, ROA, PBV, PER